The Old Roots of the Italian Health Legislation - Bassetti, Caterina (Mediterranean Journal of Social Sciences, 2011)
Current Italian Health legislation is a paradigmatic example of a system based on the fundamental principles of the safeguardand right to individual health. This raises the question of its evolution and gradual shaping stemming from very old and deep roots. Sucha long process started in the second half of the 19th century, when the newly reunified Kingdom of Italy, born in 1861, started to face theissue of a very obsolete health system. A number of laws sequentially provided the regulation of physician activities and health care for allpeople in need, regardless of their economic status and without any religious or political belief distinction, and culminate in theâ€œComprehensive Law on Healthâ€ enacted in 1934. These whole systems of laws have oriented the legislation on health care andorganization, becoming a fundamental landmark until the promulgation of the Italian Constitution in 1948.